EVALUATION OF THE IMPLEMENTATION OF GREEN CITY ATTRIBUTES IN HOUSING BUILT BY DEVELOPERS IN PALANGKA RAYA - Indrabakti Sangalang; I Kadek Mardika Muran (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2026)
The Ministry of Housing and Settlement encourages subsidized housing developers to obtain green building certificates, with the hope that environmentally friendly housing will provide added value in terms of health and energy efficiency. This is in line with two Sustainable Development Goals (SDGs), namely SDG 7 (Affordable and Clean Energy) and SDG 11 (Sustainable Cities and Communities), with a focus on green city planning, affordable and sustainable housing, and green buildings (energy efficiency). Based on SDGs 7 and 11, this study aims to evaluate subsidized housing areas built by developers in Palangka Raya to determine whether they meet green city requirements and whether the houses that have been built meet green building (energy-efficient) requirements. To achieve these objectives, the research methods used are descriptive qualitative and simulation using EDGE on selected house samples. There were four subsidized housing areas in the research location. All areas were analyzed using variables, indicators, and criteria based on Green City attributes (Green Planning and Design, Green Open Space, Green Transportation, Green Energy, Green Building, Green Waste, Green Water, and Green Community). The analysis results show that the housing areas that were the location of the research did not pay attention to green city attributes in their housing development, particularly in green transportation, green energy, green waste, green water, and green community. Furthermore, this study conducted an analysis and simulation process on a sample of one house to obtain more detailed results on the extent to which developers pay attention to green building (energy-efficient) principles in the design of the houses they build. The results show that energy efficiency is only contributed by the material aspect.